Characteristics and strategies of a consistently profitable proprietary day trader at bursa Malaysia / Saw Imm Song, Ei Yet Chu and Tian So Lai - Song, Saw Imm; Chu, Ei Yet; Tian, So Lai (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
Proprietary day trading is relatively new in Malaysia. This study looks into the background characteristics, strategies, behaviour of an above average proprietary trader and factors that determined her success. Recent literature in the developed markets found that the majority of the day traders failed in the first year of trading. Few studies have looked into the winning characteristics and strategies of the traders. Contrary to the findings on failed traders, who traded actively, speculatively, and to their detriment, this case study found that a successful trader on the other hand is highly attentive and disciplined. On average the trader had executed approximately 20 counters per day for  about 100 transactions. More than 50% of the roundtrips transactions were completed within half an hour and 70% were completed within 2 hours.  The trader was most active in the morning for buy transactions and the majority of the roundtrips were completed in the afternoon. The trader usually holds large positions only for shorter periods to minimise huge losses and disposition effect.  It was evident that the trader employs scalping strategies that she profits from very short run and small movement of prices rather than employing fundamental analysis which requires longer term investment horizon. If the trader made profits in the morning, the likelihood is the trader will be more aggressive in the afternoon trades. The regression results reveal that factors that significantly explained the profitability of the trader were the transaction values and the time entering the trades. Market sentiment and duration of holding time do not significantly explain the profitability made by the trader. It shows that in a bullish market, the trader tended to trade more transactions; however that does not contribute significantly to the profits made.